2021
DOI: 10.1016/j.parkreldis.2021.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson's disease may worsen outcomes from coronavirus disease 2019 (COVID-19) pneumonia in hospitalized patients: A systematic review, meta-analysis, and meta-regression

Abstract: Background Parkinson’s Disease (PD) is among one of the common comorbidities in older patients. People with PD may be more vulnerable to severe pneumonia, due to the impairment of pulmonary function. Currently, the association between PD and COVID-19 is not yet established. This study aims to analyze the relationship between PD and in-hospital outcomes of COVID-19. Materials and Methods We systematically searched the PubMed and Europe PMC database using specific keyword… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 42 publications
0
45
0
Order By: Relevance
“…A study showed that ACE2 has an important salutary function: ACE2 limits several detrimental effects, including vasoconstriction and enhanced inflammation and thrombosis, but it is markedly downregulated by the entry of SARS-CoV-2 into cells, which may be especially detrimental in elderly individuals with age-related baseline ACE2 deficiency [ 24 ]. In addition, compared with younger COVID-19 patient groups, the elderly (≥65 years) patient population had the highest risk of severe or critical illness, intensive care use, and respiratory failure and the longest hospital stay, which may be partly due to their higher incidence of comorbidities (such as dementia and Parkinson's disease) and age-related degeneration of the immune system (known as immunosenescence) and hence impaired immunity to SARS-CoV-2 [ [25] , [26] , [27] ].…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that ACE2 has an important salutary function: ACE2 limits several detrimental effects, including vasoconstriction and enhanced inflammation and thrombosis, but it is markedly downregulated by the entry of SARS-CoV-2 into cells, which may be especially detrimental in elderly individuals with age-related baseline ACE2 deficiency [ 24 ]. In addition, compared with younger COVID-19 patient groups, the elderly (≥65 years) patient population had the highest risk of severe or critical illness, intensive care use, and respiratory failure and the longest hospital stay, which may be partly due to their higher incidence of comorbidities (such as dementia and Parkinson's disease) and age-related degeneration of the immune system (known as immunosenescence) and hence impaired immunity to SARS-CoV-2 [ [25] , [26] , [27] ].…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, the mortality rates of COVID-19 infection for people aged over 70 are 12.8% in Italy and 8.0% in China (14). Further, the mortality of COVID-19 infection is highly associated with chronic diseases, especially those that tend to be more common among older adults, such as cardiovascular disease, dementia, Parkinson's disease, and cancer (14)(15)(16)(17). Given their increased risk, older adults may be more fearful of COVID-19 which could, in turn, contribute to the increased incidence of stress and anxiety associated with the COVID-19 pandemic (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…They may present afebrile with non-respiratory symptoms, such as delirium or isolated functional decline without any obvious physical symptoms. [26][27][28] These atypical presentations of COVID-19 may impede the early recognition of the disease, increase COVID-19 spread, and mortality. Additionally, although some comorbidities have been reported to be associated with critical illness and mortality, most previous studies did not rank their importance with respect to other laboratory variables.…”
Section: Discussionmentioning
confidence: 99%